(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Benzothiazole is one of the most important heterocyclic compound, weak base, having varied biological activities and still of great scientific interest now a days. They are widely found in bioorganic and medicinal chemistry with application in drug discovery. In the present study some novel benzothiazole derivatives were synthesized according to the scheme. All the synthesized benzothiazole derivatives have been characterized by using elemental analysis, FT-IR, 1HNMR, 13C NMR spectroscopy and further supported by mass spectroscopy. Purity of all the compounds has been checked on thin layer chromatographic plate and HPLC technique. All the synthesized compounds were tested for their antibacterial and antifungal activity (MIC) in vitro by broth dilution method with two Gram-positive bacteria, two Gram-negative bacteria and two fungal strains. The biological activities of the synthesized compounds have been compared with standard drugs Ciprofloxacin and Flucanazole. Analgesic activities were tested by Tail-flick method and Writhing method. The anti-pyretic activity was evaluated using Brewer’s yeast induced pyrexia in rats. The compounds exhibited significant and moderate antibacterial, antifungal, analgesic and anti-pyretic activities. These compounds can be further exploited to get the potent lead compounds. The detailed synthesis and the antimicrobial screening of the new compounds are reported.